PERBANDINGAN MOTIVASI BELAJAR MATEMATIKA SISWA SMA BERDASARKAN WAKTU BELAJAR - Fahmi Rizqi Nashrullah; Aries Nur Shandy; Yosi Pebriana; Gevin Rifauldy Lopez (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This research is based on the assumption that differences in study time affect students’ motivation to learn mathematics at the senior high school level. We believe that choosing an appropriate study schedule enhances students' motivation to learn mathematics. The purpose of this study is to analyze the differences in mathematics learning motivation between students who attend classes in the morning and those who attend in the afternoon. The research employs a quantitative approach using a comparative survey method. The population consists of 11th-grade science students (XI IPA) at MAN 1 Kota Cirebon in the 2023/2024 academic year. The research sample includes 34 students from class XI IPA 1 (morning class) and 34 students from class XI IPA 2 (afternoon class), selected using purposive sampling. Data were collected using a mathematics learning motivation scale. Prior to hypothesis testing, normality and homogeneity tests were conducted as prerequisites. The hypothesis was tested using an independent sample t-test. The results of the study indicate a significant difference in mathematics learning motivation between students who study in the morning and those who study in the afternoon, with a significance value of 0.040.